Enovoltaics: Symbiotic integration of photovoltaics in vineyards - Padilla, Javier; Toledo, Carlos; Abad, José (Frontiers in Energy Research, 2022)
In this study, we propose the symbiotic integration of photovoltaic (PV) systems into previously built vineyards structures, so as to reduce land intervention, visual impact and costs while suppressing impact over crop production and quality. For this purpose, we have identified grape trellises as an ideal crop type to implement this concept based on a simulation study that analyzes the shading patterns and the PV energy generation of different PV design configurations using Photovoltaic Geographical Information System’s solar radiation data and system performance tool. Our proposal consists in the vertical integration of photovoltaic surfaces over the vines, using the same trellis structure, therefore minimizing cost and land building. We found that a ratio between row distance and trellis height equal or greater than 1.5 allows for the PV integration without generating significant shadowing between consecutive lines, while vertical orientation of the panels allows complete irradiation to the plants below. Different module configurations have been proposed and evaluated, resulting in a range of 40–60% installable capacity (compared to a ground mounted installation) with negligible shadowing over the leaves and grapes. Land equivalent ratio for the proposed architectures ranges between 1.27–1.50, therefore confirming the viability of this proposed agrivoltaic solution.